Examining Mental Health Differences Between Transgender, Gender Nonconforming, and Cisgender Young People in British Columbia - Pattison, Rachal; Puyat, Joseph H.; Giesbrecht, Allison; Zenone, Marco; Mathias, Steve; Barbic, Skye (Frontiers in Psychiatry, 2021)
Foundry is an integrated service network delivering services to young people across British Columbia, Canada. To better understand the needs of transgender and gender nonconforming young people accessing Foundry – this study compares rates of mental health distress between transgender and gender nonconforming young people and cisgender young people accessing services and examines the extent to which race may have amplified the association between transgender and gender nonconforming identity and mental health distress. We analyzed the difference using a two-sample t-test. We used stratified simple linear regression to test the association of race with transgender and gender nonconforming identity and mental health distress. Participants were recruited from a network of community health centers in British Columbia, Canada. The quantitative sample (n=727) had a mean age of 21 years (SD=2), 48% were non-white, 51% were white and 77% were from Metro Vancouver. Compared to cisgender young people, transgender and gender nonconforming young people reported significantly higher levels of mental health distress. Transgender and gender nonconforming youth were more distressed than cisgender youth across both race strata but non-white transgender and gender nonconforming young people were not more distressed than white transgender and gender nonconforming young people. The findings from this study emphasize the need for increased education and understanding of transgender and gender nonconforming concepts and health concerns as well as on promoting intersectoral collaboration of social services organizations beyond simply health care.